2021
DOI: 10.1177/11206721211064018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of minimonovision in bilateral implantation of a novel non-diffractive extended depth-of-focus intraocular lens: Defocus curves, visual outcomes, and quality of life

Abstract: Purpose To evaluate overall patient satisfaction, spectacle independence, visual acuity, and prevalence of optical phenomena following bilateral implantation of a new non-diffractive extended depth-of-focus intraocular lens targeted for minimonovision. Methods Multicenter prospective case series. Postoperative far and near visual acuity at 3 months and patient quality of life by NEI-VFQ-25 questionnaire were assessed. Postoperative evaluation included defocus curves analysis, spectacle independence assessment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
2
12
1
Order By: Relevance
“…Tecnis Symfony with mini-monovision on the other hand achieved better UIVA and UNVA (−0.02±0.03 and 0.09±0.05 logMAR, respectively), and was as good as the diffractive trifocal IOL AT LISA Tri 839 MP. 29 AcrySof IQ Vivity with mini-monovision approach provided better binocular UIVA at 66cm and UNVA at 40 cm (0.00 to 0.06 and 0.12 to 0.23) 13 , 15 , 16 than the isofocal EDOF lens in our study. In another AcrySof IQ Vivity study without mini-monovision 27 even the monocular UNVA was as high as 0.15±0.16 logMAR, but interestingly, all patients still needed an addition of at least +1.0 D for near.…”
Section: Discussionsupporting
confidence: 51%
“…Tecnis Symfony with mini-monovision on the other hand achieved better UIVA and UNVA (−0.02±0.03 and 0.09±0.05 logMAR, respectively), and was as good as the diffractive trifocal IOL AT LISA Tri 839 MP. 29 AcrySof IQ Vivity with mini-monovision approach provided better binocular UIVA at 66cm and UNVA at 40 cm (0.00 to 0.06 and 0.12 to 0.23) 13 , 15 , 16 than the isofocal EDOF lens in our study. In another AcrySof IQ Vivity study without mini-monovision 27 even the monocular UNVA was as high as 0.15±0.16 logMAR, but interestingly, all patients still needed an addition of at least +1.0 D for near.…”
Section: Discussionsupporting
confidence: 51%
“…16 Furthermore, the mini-monovision technique has reportedly been used to improve near vision using EDoF IOLs. [17][18][19][20] Amelsfort et al 17 reported that when they adjusted emmetropia in the dominant eye and slight myopia in the nondominant eye (−0.25 D to −0.50 D), patients reported improved near visual acuity, better satisfaction, and higher spectacle independence. Additionally, Newsom et al 19 revealed that when −0.75 D myopia was targeted in the nondominant eye, near visual acuity improved by more than a line than in other related studies targeting bilateral emmetropia.…”
Section: Discussionmentioning
confidence: 99%
“…Also, as previously stated, near spectacle independence can be enhanced by using the mini-monovision approach. [17][18][19][20] However, further researchs are warranted to examine the outcomes of Eyhance IOL with the mini-monovision technique.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, UDVA and CDVA were similar between EDOF and monofocal IOL. 27,28 Earlier studies have reported monocular UDVAs of 0.1360.13, 29 0.0160.09, 30 and 0.0260.04 31 for Symfony and 0.1260.14, 28 0.0060.08, 32 , and 20.0160.07 33 Vivity. Earlier studies have reported monocular CDVAs of 20.0560.06, 30 0.0160.03, 34 and 0.0560.08 29 for Symfony and 0.0160.05, 28 20.0260.06, 32 and 20.0160.06 33 for Vivity.…”
Section: Discussionmentioning
confidence: 96%
“…27,28 Earlier studies have reported monocular UDVAs of 0.1360.13, 29 0.0160.09, 30 and 0.0260.04 31 for Symfony and 0.1260.14, 28 0.0060.08, 32 , and 20.0160.07 33 Vivity. Earlier studies have reported monocular CDVAs of 20.0560.06, 30 0.0160.03, 34 and 0.0560.08 29 for Symfony and 0.0160.05, 28 20.0260.06, 32 and 20.0160.06 33 for Vivity. Similarly, in the present study, the UDVA value was 0.0760.06 and 0.1060.06 and the CDVA value was 0.0160.03 and 0.0160.04 in the Symfony and Vivity groups, respectively.…”
Section: Discussionmentioning
confidence: 96%